2017
DOI: 10.1530/jme-17-0089
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of pro-inflammatory cytokine signalling by protein tyrosine phosphatases in pancreatic β-cells

Abstract: Type 1 diabetes (T1D) is characterized by the destruction of insulin-producing β-cells by immune cells in the pancreas. Pro-inflammatory including TNF-α, IFN-γ and IL-1β are released in the islet during the autoimmune assault and signal in β-cells through phosphorylation cascades, resulting in pro-apoptotic gene expression and eventually β-cell death. Protein tyrosine phosphatases (PTPs) are a family of enzymes that regulate phosphorylative signalling and are associated with the development of T1D. Here, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Importantly, PTPN1 inactivation by pharmacological modulation protects β-cells and primary mouse islets from cytokine-mediated cell death. These data point to a non-redundant effect of PTP regulation of cytokine signalling in β-cells in autoimmune diabetes [55].…”
Section: Applicationmentioning
confidence: 69%
“…Importantly, PTPN1 inactivation by pharmacological modulation protects β-cells and primary mouse islets from cytokine-mediated cell death. These data point to a non-redundant effect of PTP regulation of cytokine signalling in β-cells in autoimmune diabetes [55].…”
Section: Applicationmentioning
confidence: 69%
“…Importantly, PTPN1 inactivation by pharmacological modulation protects β-cells and primary mouse islets from cytokine-mediated cell death. These data point to a non-redundant effect of PTP regulation of cytokine signaling in β-cells in autoimmune diabetes [55].…”
Section: Applicationmentioning
confidence: 70%
“…Some studies reported that ablation or blockage of IFN-γ causes delayed or decreased incidence of T1D (14). IFN-γ has been found to increase the toxic effects of macrophages and T lymphocytes on β cell function (15)(16)(17). Improvement in β cell function in T1D is considered to be a result of insulin sensitivity and reduced inflammatory/autoimmune process in islets (18).…”
Section: Discussionmentioning
confidence: 99%